2008
DOI: 10.1111/j.1439-0531.2007.00948.x
|View full text |Cite
|
Sign up to set email alerts
|

GABA Control of GnRH Release from the Ewe Hypothalamus In Vitro: Sensitivity to Oestradiol

Abstract: The present study examines the involvement of GABA(A or B) receptors in gonadotrophin-releasing hormone (GnRH) release in vitro and determines whether oestradiol modulates gamma-aminobutyric acid (GABA)-GnRH interaction. Within 10 min after ewe killing, hypothalamic slices were dissected and placed in oxygenated Minimum Essential Media (MEM)-alpha at 4 degrees C; within 2 h, slices were singly perifused at 37 degrees C with oxygenated MEM-alpha (0.15 ml/min), with or without oestradiol (24 pg/ml). After 4 h eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…Basal GnRH increases in the presence of oestradiol ( Ghuman et al., 2006 ) and an adrenergic agonist increases release of GnRH that is prolonged by oestradiol ( Ghuman et al., 2008b ). In contrast, a GABA-A antagonist results in greater GnRH secretion that is higher in the absence of oestradiol ( Ghuman et al., 2008c ) concurring with in vivo studies ( Scott and Clarke, 1993 ). It is suggested that higher concentrations of oestradiol eventually decrease GABA turnover which in turn facilitates activation of GnRH neurones.…”
Section: Role Of Neurotransmitters In Ewes Subjected To Transport Insupporting
confidence: 75%
“…Basal GnRH increases in the presence of oestradiol ( Ghuman et al., 2006 ) and an adrenergic agonist increases release of GnRH that is prolonged by oestradiol ( Ghuman et al., 2008b ). In contrast, a GABA-A antagonist results in greater GnRH secretion that is higher in the absence of oestradiol ( Ghuman et al., 2008c ) concurring with in vivo studies ( Scott and Clarke, 1993 ). It is suggested that higher concentrations of oestradiol eventually decrease GABA turnover which in turn facilitates activation of GnRH neurones.…”
Section: Role Of Neurotransmitters In Ewes Subjected To Transport Insupporting
confidence: 75%
“…GABA neurons, as well as a dense plexus of GABA fibers are located within the ewe POA. In this area, GABA may directly control GnRH perikarya as GABA terminals synapse directly on GnRH cell bodies in the ewe and GABAA receptor mRNA co-localizes with GnRH neurons [28,29]. In ewe, about 44% neurons synthesizing GABA co-localize ERα in the POA and these account for 30% of all ERα-positive cells in this area [30].…”
Section: Noradrenaline and Gabamentioning
confidence: 99%